Educational Differences among Members of U.S. Catholic Religious Institutes: Evidence for Assessing Racial-Ethnic Perspectives on Racism (2019)
A growing body of theological and social science research is examining basic problems of racism within the Catholic Church. The author investigates whether educational differences among new members of Catholic religious institutes vary by race or ethnicity and whether this is indicative of racial or ethnic discrimination. The literature review examines the belief systems that underpin what people believe about the causes of inequality. Blacks and Hispanics are more likely to believe that social structures cause inequality. Whites are more likely to believe that individual efforts cause inequality. The author’s data come from a U.S. national survey of new members of Catholic religious institutes. Blacks and Hispanics had lower levels of education than Whites or Asians when they entered their institute (time one). They also had lower levels of education when they took the survey (time two). However, there are no significant differences between Blacks and Hispanics in educational level acquired as a member of their institute compared to Whites. This article explains the subtlety of racism in religious institutes and suggests that religious institutes recruit more people of color. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.